Usability Evaluation Satu Sehat Application Using Heuristic Evaluation Method - Amalia Agung Septarina; Abdul Aziis Arifiyanto; Usman Usman; Muhammad Irsyad Farikhin (Universitas Islam Raden Rahmat, Malang, 2025)
Digital transformation in the health sector aims to improve efficient, effective, and integrated services. The government has started building mobile-based applications in various fields. Satu Sehat application is one of mobile-based application developed by the Indonesian Ministry of Health. As an integrated health platform in Indonesia, faces challenges in ensuring optimal user experience. User experience is greatly influenced by a good user interface. User interface must have good usability aspect so that users will feel comfortable when using the application. This study aims to evaluate the usability of the application using the Heuristic Evaluation method, by identifying problems based on Nielsen's 10 heuristic principles. Evaluation was conducted by 5 evaluators who have expertise in interaction design, health technology, and usability analysis. The results reveal two problems in error prevention and one problem in help and documentation, which are the basis for recommendations for further development. Recommendations are given on several aspects to improve the user experience.